Mimicry and just world beliefs: Mimicking makes men view the world as more personally just. (9th December 2011) - Stel, Mariëlle; van den Bos, Kees; Sim, Samantha; Rispens, Sonja
Abstract : People's just world beliefs are related to how they feel and behave towards others: the stronger people hold beliefs that the world treats them fairly, the more they feel and act pro‐socially towards others. It is conceivable, therefore, that pro‐social feelings and behaviours towards others can strengthen people's personal belief in a just world, especially when people expect these positive feelings to be returned. Because mimicry enhances pro‐social feelings towards others, we argue that mimicry may strengthen peoples' personal just world beliefs via positive feelings for the mimicked person and the expectation that these positive feelings are returned. Moreover, we expect these effects to be more pronounced for men because men have stronger reciprocity beliefs than women. The results of three studies supported this line of reasoning, showing that mimicry made men believe more strongly that the world is personally just to them. Further support for our line of reasoning was obtained by positive feelings for the (non)mimicked person (Study 2) and reciprocity beliefs (Study 3) mediating the effects. Taken together, the findings suggest that mimicry makes men view the world as more just.